High prevalence of PI resistance in patients failing second-line ART in Vietnam. (11th December 2015) - Thao, Vu Phuong; Quang, Vo Minh; Day, Jeremy N.; Chinh, Nguyen Tran; Shikuma, Cecilia M.; Farrar, Jeremy; Van Vinh Chau, Nguyen; Thwaites, Guy E.; Dunstan, Sarah J.; Le, Thuy
Abstract: Background: There are limited data from resource-limited settings on antiretroviral resistance mutations that develop in patients failing second-line PI ART. Methods: We performed a cross-sectional virological assessment of adults on second-line ART for ≥6 months between November 2006 and December 2011, followed by a prospective follow-up over 2 years of patients with virological failure (VF) at the Hospital for Tropical Diseases, Vietnam. VF was defined as HIV RNA concentrations ≥1000 copies/mL. Resistance mutations were identified by population sequencing of the pol gene and interpreted using the 2014 IAS-USA mutation list and the Stanford algorithm. Logistic regression modelling was performed to identify predictors of VF. Results: Two hundred and thirty-one patients were enrolled in the study. The median age was 32 years; 81.0% were male, 95.7% were on a lopinavir/ritonavir-containing regimen and 22 (9.5%) patients had VF. Of the patients with VF, 14 (64%) carried at least one major protease mutation [median: 2 (IQR: 1–3)]; 13 (59%) had multiple protease mutations conferring intermediate- to high-level resistance to lopinavir/ritonavir. Mutations conferring cross-resistance to etravirine, rilpivirine, tipranavir and darunavir were identified in 55%, 55%, 45% and 27% of patients, respectively. Higher viral load, adherence <95% and previous indinavir use were independent predictors of VF. The 2 year outcomes of the patients maintained on lopinavir/ritonavir included: death, 7 (35%); worsening virological/immunological control, 6 (30%); and virological re-suppression, 5 (25%). Two patients were switched to raltegravir and darunavir/ritonavir with good HIV control. Conclusions: High-prevalence PI resistance was associated with previous indinavir exposure. Darunavir plus an integrase inhibitor and lamivudine might be a promising third-line regimen in Vietnam.